2008
DOI: 10.1080/08860220802212353
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sE-Selectin and sICAM-1 as Parameters for Renal Function

Abstract: Introduction. In order to monitor acute renal failure, intensive care patients were examined, and routine as well as specialized parameters were compared. Materials and Methods. Thirty-three patients at the Surgical Intensive Care Unit (ICU) were examined daily over the entire period for which they stayed in the ICU. The patients were retrospectively classified as being either with or without acute renal failure. Group 1 consisted of 22 patients who resided in the ICU for 11-15 (median 14) days without ARF. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…This is consistent with the established relationship between E-selectin gene polymorphism or serum soluble E-selectin level and atherosclerotic vascular disease, such as coronary heart disease, ischemic stroke and kidney injury. 6,17,18 Therefore, E-selectin is intricately involved in the etiology of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the established relationship between E-selectin gene polymorphism or serum soluble E-selectin level and atherosclerotic vascular disease, such as coronary heart disease, ischemic stroke and kidney injury. 6,17,18 Therefore, E-selectin is intricately involved in the etiology of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating their use as biomarkers reveal that they can be used to monitor endothelial damage of specific organs (such as L-selectin for ARDS) [24]. Soluble ICAM-1 and soluble E-selectin can be used as additional parameters indicating [25]. De Pablo et al showed that glycocalyx damage could be predicted by markers ICAM-1, which at ICU admission, sE-selectin, sVCAM-1, and sICAM-1 in patients with infectious SIRS were significantly higher than that found in patients with non-infectious SIRS [26].…”
Section: Comparison Between Groups Of Variables On Day 0 and Day 3 Ic...mentioning
confidence: 99%
“…The results suggest that during the process of ARF, PMN in spleen tissue increased robustly, which may be involved in the hemorheological disturbances 15 or the overexpression of intercellular adhesion molecules. 17 The PMN sequestrated in spleen tissues can release proinflammatory mediators and therefore arouse inflammatory cascade effects. These events will exacerbate the excessive production of free radical species.…”
Section: Discussionmentioning
confidence: 99%